Tradisi Menulis Kaligrafi Arab dan Identitas Islam Nusantara - Ahmad Tholabi Kharlia (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2006)
After Al-Qur'an is revealed to the prophet Muhammad saw, the Arab who did not know any more about the letter of the alphabet (written script) develop very fast. An art of the beautiful Arabic handwriting (islamic Caligraphy) in various kinds such as Naskh, Kufi, Riq'ah, Diwani, and Tsulus is getting more developed to other countries including Indonesia.